Poster 240: Pediatric Meniscal Repair Patients are Ready to Return to Sport Six Months after Surgery According to Isokinetic Dynamometry Testing: A Retrospective Review. Issue 7 (30th July 2022) - Clark, Kenneth; Brunst, Caroline; Dibartola, Alex; Cavendish, Parker; Milliron, Eric; Kaeding, Christopher; Duerr, Robert; Magnussen, Robert; Flanigan, David; Swinehart, Steven
Objectives: The incidence of meniscal injures in the pediatric population has been increasing over the past decade. This is likely due to more rigorous athletic activity, earlier sports specialization, year-round competition, and increasing awareness of and screening for these injuries. Many meniscal tears occur during sporting activity, and the goal of surgery is to return an athlete to play (RTP). Strength symmetry is a RTP criteria when considering return to cutting and pivoting sports. Isokinetic dynamometry testing is often done for ACL reconstruction recovery but there is currently little literature on its use in meniscal repair protocols for RTP. The purpose of this study was to establish appropriate knowledge and expectations for RTP following meniscal repair in patients ages 18 and under. It was hypothesized that patients would not meet RTP criteria based on dynamometry testing at four months post-op, but would at six months post-op. Methods: Electronic medical records were reviewed to identify patients who underwent meniscus repair at a single academic institution between 2009 and 2018. Patients were included if 18 years of age or under at the time of surgery and had concurrently undergone dynamometry testing at 4 and 6 months post-operatively. Records were reviewed for demographic data including age, sex, body mass index (BMI), and sports played. Isokinetic dynamometry testing measured quadriceps and hamstring strength at 60°/sec and 300°/sec (ft/lbs). Limb symmetry index (LSI (%)) was calculated [(involved/uninvolved) x 100%] and eligibility for RTP was deemed an LSI >85%. Results: A total of 473 patients were identified who underwent meniscus repair and dynamometry testing. Twenty-three patients met all inclusion criteria for analysis. The mean age was 16±1.24 years, with sex distribution being 52% male and 48% female. The mean BMI of 24.3±4.47. Athletes participated in the following sports (Tegner Activity Scale: 7 or higher): basketball, football, soccer, lacrosse, wrestling, volleyball, softball, track and field; including three multi-sport athletes. 83% of patients had concurrent ligamentous reconstruction at the time of meniscus surgery. Conclusions: Only 50% of patients with isolated meniscus repair met RTP criteria at 4 months. However, 75% or greater met criteria at 6 months (Table 1). Additionally, patients with a concurrent ligamentous repair were challenged to meet RTP criteria at both time points. These data suggest that formal physical therapy for greater than 6 months is beneficial to achieve suggested RTP strength criteria for those with isolated meniscus repair; furthermore, those with meniscal repair and concurrent ligamentous reconstruction will require longer episodes of care to meet RTP criteria. Future studies are needed to examine factors that lead to earlier RTP, such as; type of tear, type of sport, level of competition, and quadriceps/hamstring strength prior to surgery. Table 1. Isolated Meniscus Table 2. Concurrent Ligament Reconstruction